Post-COVID 19 narcolepsy, a case report (Research, Society and Development, 2025)
Objective: The aim of this article was to report the case of a teenager who developed narcolepsy after infection with COVID-19 and there were no other infections that could justify the case. Methodology: information was obtained through medical record review, recording of diagnostic methods and literature review. Case report: Patient B.M.C, female, 16 years old, presented to the clinic due to episodes of narcolepsy. Final considerations: the reported case and publications raised shed light on the possibility that COVID-19 infection also causes narcolepsy, which is a new means of triggering this pathology.